Online Structural Health Monitoring of Rotating Machinery via Ultrasonic Guided Waves - Ming Li; Guang Meng; Hongguang Li; Jianxi Qiu; Fucai Li (Shock and Vibration)
This paper focuses on the establishment of the online structural health monitoring strategy for rotating shafts using ultrasonic guided waves. The dispersion of cylindrical shaft is investigated and a conclusion that the longitudinal ultrasonic wave propagating along the cylindrical shaft can hardly be interfered by the rotation is obtained. The experimental system and the numerical simulation model have been constructed, based on the fact that the experimental research and the numerical verification have been conducted intensively. The strategy can be concluded no matter the cracked rotor is at rest or rotating. Comparing with the same rotor without crack, the amplitudes of the guided wave packages descend along the transmission path and the symmetric path where crack exists; however, the amplitude of the wave packages will ascend along the other transmission paths.